Three notebooks by Florence O'Donoghue containing notes on witnesses dealt with in the course of his work on Cork and Kerry for the Bureau of Military History, - O'Donoghue, Florence, 1895-1967 (1947)
Notebooks are labelled '1', '2' and 'Kerry'.